The political and legal role of international straits (The Strait of Hormuz as a model) - AL-ALAN, DR. ELHAM (The journal of contemporary issues in business and government, 2021)
Countries have been interested in the agreements regulating the straits, due to their strategic and economic importance and to ensure the safety of navigation in them, during the passage of ships and aircraft in the strait and not to close them. Given that closing the strait will threaten the security of maritime navigation and target the economic interests of all countries crossing the strait. As of the Middle Ages and passing by 1958 Geneva Convention, and up to the 1982 United Nations Convention on the Law of the Seas, countries have been trying to conclude a compromise between the international straits riparian states, whether through transit or safe passage, however, the agreements, despite their legal binding power, were unable to oblige some countries to ratify them. The vital and political interests have played a prominent role in using the straits as a political pressure card in favour of some pending issues between countries. On the other hand, the Iranian nuclear file crisis is still present to coincide with the Iranian threats to close the strait. Thus, the issue has had a political dimension affected by the result of the escalation between the two countries against the background of the presence of the former US President Donald Trump who imposed the unprecedented and severest sanctions in the history of America on the Iranian Republic. After that, President Biden assumed the new US presidency term and seeks to find a legal political harmony to compromise the crisis out of the perspective of diplomacy.